EUROPEAN ASSOCIATION OF PERINATAL MEDICINE (EAPM) Position statement: Use of appropriate terminology for situations related to inadequate fetal oxygenation in labor - Vayssière, Christophe (Elsevier, 2025)
In high-resource countries, adverse perinatal outcomes are currently rare in term, non-malformed fetuses, undergoing labor, but they remain a leading cause of medico-legal dispute. Precise terminology is important to describe situations related to inadequate fetal oxygenation in labor, to ensure appropriate communication between healthcare professionals and adequate transmission of information to parents. This position statement provides consensus definitions from European perinatologists and midwives regarding the most appropriate terminology to describe situations related to inadequate fetal oxygenation in labor: suspected fetal hypoxia, severe newborn acidemia, newborn metabolic acidosis, and hypoxic-ischemic encephalopathy. It also identifies terms that are imprecise or nonspecific to this situation, and should therefore be avoided by healthcare professionals: fetal well-being, fetal stress, fetal distress, non-reassuring fetal state, and birth asphyxia.